Influence of ionic liquids on the electronic environment of atomically dispersed Ir on (MgO)(100) - FINDIK, VOLKAN (My University, 2022)
Recently, ionic liquids (ILs) have been used as ligands for single-site Ir(CO)(2) complexes bound to metal-oxide supports because of their electron-donor/acceptor capacities. The combined effects of supports and ILs as ligands may pave the way to the tuning of the surrounding electronic properties to increase electron-donor/acceptor efficiency in metal-oxide supported Ir(CO)(2) complexes. Herein, we have used Density Functional Theory to model Ir(CO)(2) complexes bound to MgO supports with and without the presence of an IL to explain the role of ILs in modifying the electronic structure of the supported complex. Comparison of the nu(CO) band stretching frequencies with experimental results has led to the rationalization of the factors driving the interactions between the IL, the support, and the catalyst as well as the justification of the methodology for further studies.
Keywords: Fizik; Atom ve Molekül Fiziği; Kimya; Fizikokimya; Temel Bilimler; Physics; Atomic and Molecular Physics; Chemistry; Physical Chemistry; Natural Sciences; KİMYA, FİZİKSEL; Temel Bilimler (SCI); FİZİK, ATOMİK, MOLEKÜLER VE KİMYASAL; CHEMISTRY, PHYSICAL; CHEMISTRY; Natural Sciences (SCI); PHYSICS, ATOMIC, MOLECULAR & CHEMICAL; PHYSICS; Yüzeyler ve Arayüzler; Kimya (çeşitli); Genel Kimya; Fiziksel ve Teorik Kimya; Atom ve Moleküler Fizik ve Optik; Yüzeyler, Kaplamalar ve Filmler; Fizik Bilimleri; Surfaces and Interfaces; Chemistry (miscellaneous); General Chemistry; Physical and Theoretical Chemistry; Atomic and Molecular Physics, and Optics; Surfaces, Coatings and Films; Physical Sciences